ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL PADA MATERI HIMPUNAN - Shelly Fitri Andini; Rina Marlina (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The aim of this research is to analyze the level of mathematical communication skills in junior high school on set material. The research is for seventh grade student from one the school in Kabupaten Karawang. with the total of students are 16 and using descriptive qualitative method. Accumulation data was obtained by giving a test of mathematical communication skills in the form of 5 question essay about set material. The accumulation data technique for this researh is using three stateg, those stage are the first stage is reduction data, the second stage is explaining the data and the third stage is evaluation. The result of the study from the 5 questions of the mathematical communication skills are obtaining result from question number 1 to 4 belong to the low category with a percentage of ≤ 33%. While the result from question number 5 belong to the medium category with a percentage of > 33%. It can be concluded from the result obtained that skills of mathematical communication junior high school student are in the low category because there are four questions belong to the low category with a percentage of ≤ 33%.